Sistem Pendukung Keputusan Pemberian Kredit Rumah Sejahtera Pada Nasabah Bank Pembangunan Daerah Kalimantan Timur dengan Metode TOPSIS - Jumadi, Agus; Arifin, Zainal; Khairina, Dyna Marisa (JSINBIS (Jurnal Sistem Informasi Bisnis), 2014)
One of the most basic of human needs is the house as a place to live and settle. To be able to have a house requires a considerable cost. Therefore, we need a party as an intermediary to ease of payment to purchase of the house. The intermediary in this case is Bank. In this study, the Regional Development Bank (BPD) in East Kalimantan into a bank that was taken as a reference to obtain a loan writers Mortgage Prosperity. During this time , the decision making is done by the analysis of credit (account officer) , always has a lot of obstacles, such as the decision-making process is not effective (use of longer periods of time , effort and money is wasted) , human error and the possibility of collusion between customers and officers of the Bank. Web-based system is built so that users can easily access the system anytime and anywhere. Provision of decision support systems Prosperous Home Lending (KRS) for customers of Regional Development Bank (BPD) in East Kalimantan with Technique For Others Reference by Similarity to Ideal Solution (TOPSIS) methods as a determinant of final calculation from value of available alternatives. TOPSIS is not only consider the closest distance to the ideal solution, but also takes into account the distance to the farthest negative ideal solution to determine the selected alternative. Result from this study is an application decision support facilitate decision-making to facilitate decision-making releated to the problem of determining the recipient of a prosperous home loans in BPD Kaltim, so it can provide decision analysts credit home loans prosperous and appropriately based systems. Keywords : Decision Support System; Prosperous Home Lending Development; Topsis Method